2014
DOI: 10.1016/j.jms.2014.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Rotational state analysis of AlH+ by two-photon dissociation

Abstract: We perform ab initio calculations needed to predict the cross-section of an experimentally accessible (1 + 1 ′ ) resonance-enhanced multiphoton dissociation (REMPD) pathway in AlH + . Experimenting on AlH + ions held in a radiofrequency Paul trap, we confirm dissociation via this channel with analysis performed using time-of-flight mass spectrometry. We demonstrate the use of REMPD for rotational state analysis, and we measure the rotational distribution of trapped AlH + to be consistent with the expected ther… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…In all of these experiments, the ions are ejected radially from the trap. Seck et al coupled a LQT to a TOF-MS in which the ions are accelerated along the trap axis into the TOF-MS by applying a potential gradient using the endcaps of the ion trap [25]. The advantage of this setup is the separation of RF and highvoltage electrodes but the mass resolution for heavy ions in multi-component Coulomb crystals seems limited.…”
Section: Introductionmentioning
confidence: 99%
“…In all of these experiments, the ions are ejected radially from the trap. Seck et al coupled a LQT to a TOF-MS in which the ions are accelerated along the trap axis into the TOF-MS by applying a potential gradient using the endcaps of the ion trap [25]. The advantage of this setup is the separation of RF and highvoltage electrodes but the mass resolution for heavy ions in multi-component Coulomb crystals seems limited.…”
Section: Introductionmentioning
confidence: 99%
“…In experiments where the aluminium ion spends about half the time in the 3 P 0 clock state, we observe that Al + ions are replaced by molecular ions of mass m=28u on a time scale of about 15min. While we cannot unambiguously identify the ion species, it seems likely that Al + reacts with H 2 background gas molecules to form AlH + [42,43]. The resulting short time span for probing the clock transition in Al + , in combination with long Al + reloading times [32], prevented us from investigating the clock transition more thoroughly.…”
Section: Discussionmentioning
confidence: 98%
“…This resolution is sufficient to observe the individual isotopes of the trapped molecular ions and has allowed isotopically resolved chemistry and spectroscopy. Several other groups have also recently developed ToFMS capabilities using variations of the technique [66][67][68][69]. In addition to being a powerful measurement capability, we have found that in day-to-day operation the ToFMS provides an incredibly useful diagnostic tool.…”
Section: Detection Tof-ms and Spectroscopymentioning
confidence: 94%